2010
DOI: 10.3109/14764172.2010.503787
|View full text |Cite
|
Sign up to set email alerts
|

Patient compliance as a major determinant of laser tattoo removal success rates: A 10-year retrospective study

Abstract: The use and success of high-energy, short-pulse, Q-switched lasers for tattoo removal has been well demonstrated. Three types of lasers are currently commercially available for tattoo removal: the Q-switched ruby laser (694 nm), the Q-switched alexandrite laser (755 nm) and the Q-switched Nd:YAG laser (532 nm and 1064 nm). Multiple parameters such as tattoo type, color, location, and patient skin type dictate which laser is optimal in each patient. Despite the demonstrated efficacy of these modalities, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Total clearance of a tattoo is not often seen and one study reported that only three of 238 paying patients achieved this goal. [ 8 ] Thus, a constant endeavour is to optimise laser parameter selection, increase the efficacy of each treatment session, and minimise the total number of treatment sessions required. [ 1 2 8 ]…”
Section: Mechanisms Of Tattoo Removalmentioning
confidence: 99%
“…Total clearance of a tattoo is not often seen and one study reported that only three of 238 paying patients achieved this goal. [ 8 ] Thus, a constant endeavour is to optimise laser parameter selection, increase the efficacy of each treatment session, and minimise the total number of treatment sessions required. [ 1 2 8 ]…”
Section: Mechanisms Of Tattoo Removalmentioning
confidence: 99%
“…A recent study found that eight or more sessions are often necessary for a satisfactory result 2. Total clearance of a tattoo is rare, quoted in one study as being only three of 238 paying patients 3. In order to optimise laser parameter selection, increase the efficacy of each treatment session, and minimise the total number of treatment sessions required, an improved understanding of the mechanisms of pigment reduction is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the optimal length of laser radiation (optimal laser) in relation to different dye colors. 22 Effective tattoo removal usually requires from 8 to 16 treatments.…”
Section: Laser Tattoo Removalmentioning
confidence: 99%
“…At the same time, different dye colors have different absorption maxima, which results in the necessity to use lasers with several wavelengths. Table 1 shows the optimal length of laser radiation (optimal laser) in relation to different dye colors 22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation